Issues in the pricing of domestic and internationally-traded gas in MENA and sub-Saharan Africa - Darbouche, H (Oxford Institute for Energy Studies, 2012)
The countries of the Middle East and Africa sit on large reserves of natural gas, but their share of international trade looks unlikely to increase significantly by 2020. Fast-growing domestic demand is, in many of these countries, putting considerable pressure on domestic gas supply, resulting in reduced exports and growing import needs. Artificially-low domestic gas prices are a key feature of this state of play. They need to be reformed if these regions – especially the Middle East and North Africa – are to contribute to international gas trade more as a source of exports than as a growing demand (and import) centre. However, reforms of gas (and energy) prices remain tentative because of the political economy logic in which they tend to be rooted and in which governments appear to be locked. This is not to say that solutions do not exist – remedies can be devised based on existing experiments and country-specific circumstances. This paper analyses the political economy of domestic pricing in gas-rich developing countries in the Middle East and Africa, and chronicles the pricing mechanisms in the main export and import contracts in these regions, helping assess the disconnect between domestic prices and international prices and its implications for gas use in these regions.